(untitled) (Itinera, 2019)
This article is centred on the faux queen experimental theatre by Italian artist Senith, and on the links between this theatre and queer feminist activism in Italy. Senith is a queer drag performer from Rome, and the co-founder of the former queer drag king group Eyes Wild Drag. After the group disbanded in 2015, Senith has been performing as a solo artist in shows such as BAD ASSolo (2016) and Lo Schizzo (2017) [Squirting]. She has also been developing, transforming and enriching projects originally born within Eyes Wild Drag such as the Erotic Lunch and the Queerrida. The article will concentrate on Senith’s faux queen experimentations, trying to understand how the genre is translated/adapted for the Italian scenario and what Senith is trying to achieve with it. In doing so the article will discuss the notion of queer femininity, otherwise known as Fem or femme (Serano 2007; Dahl 2009), its genealogy within lesbian feminism, and the connection between the themes developed by faux queen performances in general and those discussed in queer transfeminist activist scenarios in Italy. These are, in particular, the invisibility of the Fem, misogyny, slut-shaming, sexism, and women’s control over their body and sexuality.